Journal of medical research Volume 111. No 2 (H. Journal of medical research, 2018)
Contents: Rapid real-time PCR for CYP2C19 and ITGB3 gene detection to optimize the use of clopidogrel and aspirin for PCI stent graft patients; Study on the hypoglycemic action of CF2 in induced type 2-like diabetic mice model; The impact of seminal zinc and fructose concentration on human sperm characteristic;...
Keywords: Y đa khoa; Tạp chí